1999
DOI: 10.1007/s002689900641
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal Extensive Esophagogastric Devascularization with Gastroesophageal Stapling for Management of Noncirrhotic Portal Hypertension: Long‐term Results

Abstract: Outside Japan portosystemic shunts have been favored as the surgical procedure of choice for the management of portal hypertension of noncirrhotic etiology. Devascularization procedures have resulted in high rebleed rates probably owing to a limited extent of devascularization. We performed this study to assess the efficacy of our modification of Sugiura's procedure for long-term control of variceal bleeding in patients with noncirrhotic portal hypertension. Forty-six patients with extrahepatic portal venous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 35 publications
6
34
1
1
Order By: Relevance
“…An operative mortality of 4%, rebleeding rate of 11% (5% variceal), esophageal stricture rate of 15% and a 5-year survival of 88% were reported [24]. The authors concluded that this modified Sugiura procedure was safe and effective for long-term control of variceal bleeding in NCPH, especially in the emergency setting and in patients with anatomy unsuitable for shunt surgery or if surgical expertise for a shunt operation is not available [24]. Orozco et al [61] from Mexico reported similar results in a selected group of patients with EHPVO (n=38) undergoing the one-stage or two-stage Sugiura procedure.…”
Section: Devascularization Procedures In Ncphmentioning
confidence: 98%
See 3 more Smart Citations
“…An operative mortality of 4%, rebleeding rate of 11% (5% variceal), esophageal stricture rate of 15% and a 5-year survival of 88% were reported [24]. The authors concluded that this modified Sugiura procedure was safe and effective for long-term control of variceal bleeding in NCPH, especially in the emergency setting and in patients with anatomy unsuitable for shunt surgery or if surgical expertise for a shunt operation is not available [24]. Orozco et al [61] from Mexico reported similar results in a selected group of patients with EHPVO (n=38) undergoing the one-stage or two-stage Sugiura procedure.…”
Section: Devascularization Procedures In Ncphmentioning
confidence: 98%
“…In a series of 68 patients (44 EHO, 22 NCPF), transabdominal extensive esophagogastric devascularization with gastroesophageal stapling was done (emergency 38; elective 30) and were followed up for a mean period of 54 months. An operative mortality of 4%, rebleeding rate of 11% (5% variceal), esophageal stricture rate of 15% and a 5-year survival of 88% were reported [24]. The authors concluded that this modified Sugiura procedure was safe and effective for long-term control of variceal bleeding in NCPH, especially in the emergency setting and in patients with anatomy unsuitable for shunt surgery or if surgical expertise for a shunt operation is not available [24].…”
Section: Devascularization Procedures In Ncphmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognosis of IPH is generally good if an effective prophylaxis and management of esophageal variceal bleeding take place [1,9]. Treatment options for esophageal varices in patients with IPH recently have become more diverse and include portal decompression procedures [4,6,10,11], devascularization procedures and splenectomy [12][13][14][15][16][17][18], endoscopic injection sclerotherapy (EIS) or variceal ligation (EVL) [6,[19][20][21], and interventional radiology [22,23]. To date, no clear consensus has been reached concerning the best method for treatment of esophageal varices due to IPH.…”
Section: Introductionmentioning
confidence: 99%